Applying Linked Open Data and ETL for Mapping and Visualization of Physical Objects in Botany - Yagui, Marcela Mauricio Mayumi; Maia, Luís Fernando Monsores Passos; Oliveira, Jonice; Vivacqua, Adriana S. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2017: Anais Estendidos do XXIII Simpósio Brasileiro de Sistemas Multimídia e Web, 2017)
The purpose of this paper1 is to show an architectural project to develop an application that aims to connect data from existing plants to available repositories on the Web, generate content and provide the mapping of these plants and museums, herbariums and research institutes engaged in studying them, highlighting their collaboration network. To this end, the ETL tool Knime was used, with the aid of LOD technology and open data extracted from GBIF, in order to provide an automatic method for creating dynamic pages where information of medicinal plants can be viewed and the mapping of the collection linked to the plant image in association with the related research institutes, providing users with a wide view of the georeferenced area.